KONSTRUKSI INFINITIF DALAM BAHASA JERMAN - Widodo, Pratomo (Diksi, 2006)
In German syntactic structure, an infinitive verb combines with a finiteverb in a verb phrase or complex verb to perform its function as the predicate of asentence. A syntactic construction which includes an infinitive form is called aninfinitive construction.Infinitive constructions in German are of two types: coherent andincoherent ones. The first type has no syntactic value and can function only as thepredicate of a sentence but the second type has a syntactic value and is a form ofquasi-sub-clause. Both types are found in some syntactic constructions.Keywords: infinitive, coherent, incoherent